THE ABYSS OF THE CONSCIOUSNESS-TIME WITHIN THE CRYSTAL-IMAGE: KRZYSZTOF ZANUSSI AND WERNER HERZOG - CÂMPEAN, Noemina (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
The paper undertakes to analyze the specificity of Gilles Deleuze’s concept of crystal-image in two films: The Structure of Crystal/ Struktura krysztalu (Krzysztof Zanussi, 1969) and Heart of Glass/ Herz aus Glas (Werner Herzog, 1976). The crystal-image offers an insight into the amorphous abyss of consciousness, but it also represents the natural culmination of image in the history of modern cinema. Whereas in Zanussi the crystal of time depicts the figure of the visionary that sees the self-castration of time, the non-actor of Herzog, with a hypnotic gaze and a heart of glass, is the only one capable of seeing the inner being of a landscape.